Factors affecting the adoption and integration of ICT as a pedagogical tool in rural primary schools - Chinaka, Gift (Midlands State University, 2020)
Information Communication Technology (ICT) is an important innovation that many education systems across the globe are embracing. ICTs are powerful tools that can be used to enhance the learning experiences of children in schools. However, there are several factors that are militating against effective utilisation of ICT in Zimbabwean primary schools. The use of computers in teaching and learning of subjects in the primary school curriculum has been greatly influenced by many factors. This study examines factors that are militating against successful adoption and integration of ICT in rural primary schools in Bradely Cluster, Shamva District in Mash-Central Province in Zimbabwe. Findings from this study will bring tremendous benefits to all stakeholders of the education system in Zimbabwe.Data in this research paper were collected using a five-item Likert-type questionnaire administered to the participants who were teachers in the cluster’s primary schools. The cluster was made up of four rural schools. Data on the level of utilisation of ICTs in teaching and learning processes as well as factors affecting the adoption and integration of ICTs were analysed using tables containing summaries of compiled data and pie charts. This study revealed that lack of infrastructure, unavailability of electricity, teacher’s lack of ICT knowledge and skills and lack of funding have emerged as key factors that are affecting the successful adoption and integration of ICTs in rural primary schools. However, issues of gender, age and teacher qualification emerged as other factors that are affecting the adoption and integration of ICTs in the cluster.